Evaluasi Penerapan Konsep Bangunan Hijau pada Kantor LLDIKTI Wilayah XIII di Banda Aceh - Fuady, Mirza; Ridwan, Nasrullah; Buraida, Buraida; Munadi, Rizal; Noer, Raedy; Kevin, M Andrian; Farrel, M Rafi; Triaputri, Allya (Universitas Syiah Kuala, 2025)
This community service activity was carried out to evaluate the application of the green building concept in the LLDIKTI Building Region XIII, Banda Aceh. The background of this activity is based on the need to encourage efficient, environmentally friendly, and sustainable building management set by the Green Building Council Indonesia (GBCI). The implementation method employs a participatory approach, incorporating technical field observations, interviews with building managers, and a review of administrative documents. The primary instrument used is the Greenship Rating Tools for Existing Buildings (EB) version 1.1, which encompasses six assessment categories: Appropriate Site Development, Energy Efficiency and Conservation, Water Conservation, Material Sources and Cycles, Indoor Space Health and Comfort, and Building Environmental Management. The results of the activity showed that the LLDIKTI Building had a relatively good score in the aspects of land management and interior comfort, but was still weak in the categories of energy efficiency and water conservation. This analysis provides an overview of the building's position in green building standards as well as strategic recommendations for improving sustainable management. Thus, this activity not only produces technical evaluations but also provides knowledge transfer to partners regarding the importance of applying green building principles.